1990
DOI: 10.1017/s0022215100113374
|View full text |Cite
|
Sign up to set email alerts
|

Delayed facial palsy following uncomplicated stapedectomy

Abstract: We report six cases of partial lower motor neurone facial palsy occurring between four and ten days after uncomplicated stapedectomy. The aetiology is unclear but recovery was rapid and complete in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 2 publications
0
13
0
2
Order By: Relevance
“…Delayed facial palsy after stapedectomy has been observed in 0.1-0.5% of operations [2,[18][19][20]. It has been estimated that the incidence of Bell's palsy worldwide varies widely ranging between 0.01 and 0.04% [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delayed facial palsy after stapedectomy has been observed in 0.1-0.5% of operations [2,[18][19][20]. It has been estimated that the incidence of Bell's palsy worldwide varies widely ranging between 0.01 and 0.04% [21].…”
Section: Discussionmentioning
confidence: 99%
“…The review of the literature on delayed ipsilateral facial palsy following uncomplicated stapedectomy (considering the present case) includes 27 cases (12 males, 8 females and 7 cases of unspecified gender) aged from 19 to 71 years (in the 19 cases providing details, the average was 45 years, SD 14 years) (table 1) [2,3,11,[18][19][20][22][23][24][25]. Three of the procedures were revisions of stapedectomy [18,20,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible pathogenetic mechanisms resulting in the development of a delayed facial weakness are still poorly understood. Based upon interval evolution of delayed dysfunction, Lalwani et al [6] suggested that neural edema may be the cause of the deterioration in facial function observed in the early postoperative period (1-3 days), while a reactivation of a dormant (herpes virus) [3,9,12,14,15] could explain a delayed palsy that occurs later. In such a condition, prophylactic administration of antiviral agents (such as aciclovir) has been suggested as well as the admnistration of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the demonstrated incidence of sensitivity to neomycin in patients with chronic external otitis has risen progressively from an incidence of around 8% in the early 1970s to 35% in the early 1990s [46][47][48][49]. Topical sensitization may manifest as a fairly florid and obvious reaction with erythematous and vesicular eruption involving the lobule, entire auricle, and sometimes the surrounding tissues.…”
Section: Treatmentmentioning
confidence: 99%